2007
DOI: 10.1093/jn/137.11.2366
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Increases the Expression of the Iron Regulatory Hormone Hepcidin in HuH7 Human Hepatoma Cells

Abstract: Obesity is a major global health problem and is associated with low-grade inflammation and, in a number of cases, poor iron status. We speculated that the adipokine leptin might play a role in regulating iron metabolism in the overweight population because it shares a number of common biological features with IL-6, a major factor in the development of the anemia of chronic disease via its stimulatory actions on the production and release of the iron regulatory hormone hepcidin. To test this hypothesis, we expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
2
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 42 publications
3
123
2
5
Order By: Relevance
“…Leptin has been shown to stimulate hepcidin m-RNA production in a similar manner as interleukin-6. 5 Therefore, the possibility exists that, in the context of obesity, leptin may exert a major effect in modulating hepcidin levels, appearing important in linking obesity and hepcidin with the iron status. This is in agreement with the lack of correlation between serum hepcidin and interleukin-6, recently reported in obese women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin has been shown to stimulate hepcidin m-RNA production in a similar manner as interleukin-6. 5 Therefore, the possibility exists that, in the context of obesity, leptin may exert a major effect in modulating hepcidin levels, appearing important in linking obesity and hepcidin with the iron status. This is in agreement with the lack of correlation between serum hepcidin and interleukin-6, recently reported in obese women.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, pro-inflammatory cytokines, such as interleukin-6, but also the adipokine leptin, stimulate hepcidin transcription through JAK-STAT3 interactions. 4,5 Three recent studies have shown that, both in obese women and in obese children, serum hepcidin levels were significantly higher compared with normal weight controls and have focused on the hepcidin-mediated inhibition of dietary iron absorption in obese patients. [6][7][8] To gain insight into the link between obesity and hepcidin, we performed an intervention study in a group of obese children and evaluated if body mass index (BMI) decrease may reduce circulating hepcidin levels, increasing, therefore, iron absorption and improving iron status.…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, circulating leptin is higher in overweight subjects, 48 and leptin increases hepcidin expression by liver cells in vitro via JAK/STAT signaling. 24 Similarly, lipocalin-2 is an iron-binding protein that is upregulated by inflammation and may help sequester iron during infections. 49 It is produced by adipose tissue and its expression is increased in db/db (leptin receptor-deficient) obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] Although the mechanism is unclear, this may be due to lower iron intakes and/or increased iron requirements in overweight individuals. 14,23 In addition, the chronic inflammation and increased leptin production characteristic of obesity increase hepcidin secretion from the liver, 24 which, along with hepcidin produced by adipose tissue, 25 could reduce dietary iron absorption. 26 The major adverse effects of iron deficiency are impaired cognitive development in children 27 and poorer pregnancy outcome in women.…”
Section: Introductionmentioning
confidence: 99%
“…La leptina, adipoquina proinflamatoria 46 , puede operar por un mecanismo de señalización intracelular similar a la IL-6 47 . Estudios in vitro reportaron que la leptina regularía la expresión hepática de Hpc, sugiriendo que el aumento de esta adipoquina en sangre podría contribuir a los desórdenes del metabolismo de Fe 48 . En niños obesos se ha mostrado que el aumento de la producción de Hpc está mediado por la leptina 49 .…”
Section: Obesidad Y Hepcidinaunclassified